D-DEMØ, a distinct phenotype caused by ATP1A3 mutations. (October 2020) - Prange, Lyndsey; Pratt, Milton; Herman, Kristin; Schiffmann, Raphael; Mueller, David M.; McLean, Melissa; Mendez, Mary Moya; Walley, Nicole; Heinzen, Erin L.; Goldstein, David; Shashi, Vandana; Hunanyan, Arsen; et al.
Abstract : Objective: To describe a phenotype caused by ATP1A3 mutations, which manifests as dystonia, dysmorphism of the face, encephalopathy with developmental delay, brain MRI abnormalities always including cerebellar hypoplasia, no hemiplegia (Ø) (D-DEMØ), and neonatal onset. Methods: Review and analysis of clinical and genetic data. Results: Patients shared the above traits and had whole-exome sequencing that showed de novo variants of the ATP1A3 gene, predicted to be disease causing and occurring in regions of the protein critical for pump function. Patient 1 (c.1079C>G, p.Thr360Arg), an 8-year-old girl, presented on day 1 of life with episodic dystonia, complex partial seizures, and facial dysmorphism. MRI of the brain revealed cerebellar hypoplasia. Patient 2 (c.420G>T, p.Gln140His), an 18-year-old man, presented on day 1 of life with hypotonia, tremor, and facial dysmorphism. He later developed dystonia. MRI of the brain revealed cerebellar hypoplasia and, later, further cerebellar volume loss (atrophy). Patient 3 (c.974G>A, Gly325Asp), a 13-year-old girl, presented on day 1 of life with tremor, episodic dystonia, and facial dysmorphism. MRI of the brain showed severe cerebellar hypoplasia. Patient 4 (c.971A>G, p.Glu324Gly), a 14-year-old boy, presented on day 1 of life with tremor, hypotonia, dystonia, nystagmus, facial dysmorphism, and later seizures. MRI of the brain revealed moderate cerebellar hypoplasia. Conclusions: D-DEMØ represents an ATP1A3 -related phenotype, the observation of which should trigger investigation for ATP1A3 mutations. Our findings, and the presence of multiple distinct ATP1A3 -related phenotypes, support the possibility that there are differences in the underlying mechanisms.